The impact of financial distress, sustainability report disclosures, and firm size on earnings management in the banking sector of Indonesia, Malaysia, and Thailand - Revy Karina; Yanuar Nanok Soenarno (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - Does financial distress, sustainability report disclosures, and firm size have an effect on earnings management? Motivation - Researchers want to know the effect of financial distress, sustainability report disclosures, and firm size on earnings management. Idea - The purpose of this paper is to determine the impact of Financial Distress (FD), Sustainability Report (SR), and Firm Size (FS) on earnings management in the banking sector of Indonesia, Malaysia and Thailand. Data - The data for this research is taken from the financial reports, annual reports, and sustainability reports issued by the companies from 2019 to 2020. The populations in this study are banking companies listed on the Indonesian, Malaysian, and Thailand Stock Exchanges. The samples used are 43 public banking companies in Indonesia, 10 public banking companies in Malaysia, and 8 public banking companies in Thailand. Tools - This study uses a regression model made with E-Views 10. Findings - The results show that financial distress has a significant influence on earnings management, sustainability reports have no influence on earnings management, and firm size has an influence on earnings management, but only in Malaysia's and Thailand's banking companies. Contribution - The results of this study are expected to provide ideas and reference materials regarding financial distress, disclosure of corporate sustainability reports, firm size, and earnings management practices. For companies, especially from the banking sector, this study is expected to provide information that they must be careful in reporting financial statements that will be published considering that banking companies are a business entity that receives and safeguards money owned by the public and lends out this money in the form of loans or credits. Banks are the main financial institutions in the financial system that drive the economy in a country. If a banking company experiences a financial crisis, it will have a wide impact on the financial system and economic sector in a country. The results of this study are also expected to help investors make investment decisions in a company and the results of this study are expected to help creditors in making funding decisions in a company.
Keywords: M41; 650; earnings management; financial distress; sustainability report; firm size